FAME, FICTION, AND FALLACY: UNMASKING THE DUALITIES OF INDIAN POPULAR CULTURE IN SHOW BUSINESS - Kumar, Sooraj; Rajan S., Seema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Shashi Tharoor’s Show Business (1992) is a sardonic investigation of the Indian film industry, offering a piercing analysis of celebrity culture, the commodification of art, and the indistinct boundaries between illusion and reality. It is through the rise and fall of its protagonist, Ashok Banjara, a Bollywood superstar turned politician, that the novel delves into the moral compromises and ethical impasses inherent in the quest of fame and power. Tharoor employs a metafictional narrative style, combining the protagonist’s introspective monologues with exaggerated film scripts that mirror the dramatic episodes of his life. These scripts not only parody Bollywood tropes but also emphasize the performative nature of identity in both cinema and real life. Combining humour, irony, and pathos, Tharoor’s narrative serves as both an engaging story and a profound commentary on the intersections of culture, politics, and human ambition. The novel critiques the socio-political fabric of India, highlighting the pervasive influence of media and the public’s complicity in perpetuating the cult of celebrity. Show Business, at its core, is a tale about the alluring and seductive stardom and the cost of living in a world where spectacle often trumps substance.